Perception of college students on the level of importance of factors to their self-disclosure in online communication - M. Ilar 1, Stephanie Camille; R. Realgo 2, Bryan (Social Sciences, Humanities and Education Journal (SHE Journal), 2024)
This study applied mixed-methodology and investigated the importance of time, text composition, and tone to College of Arts and Sciences students of Mariano Marcos State University, Philippines in their self-disclosure in online communication, specifically in gauging and choosing co-communicators, since people interpret factors differently depending on the people involved or the context of the conversation. It revealed that people recognized some situations involving the factors as important and some as slightly important. Time was mostly perceived as important; text composition was perceived both slightly important and important; and tone was perceived as important by most in self-disclosure. Meanwhile, the qualitative interview reveals varying themes about how each factor affects communication. The findings unfold more knowledge about how the factors affect self-disclosure of communicators online, which may create better relationships within these platforms. Findings emphasize the individuality of each person in giving importance to each factor in online communication in self-disclosure.